Psychological wellbeing and the association with burnout in a cohort of healthcare workers during the COVID-19 pandemic - Bannon, Jacqueline; Evans, Charlesnika T.; Freedman, Melanie; Lee, Cerina; Vu, Thanh Huyen; Wallia, Amisha; Wilkins, John T.; Moskowitz, Judith T.; Hirschhorn, Lisa R. (Frontiers in Health Services, 2022)
Burnout, depression, and anxiety are prevalent among healthcare workers (HCWs) during the COVID-19 pandemic and have been previously shown to contribute to poor health outcomes and reduced quality of care. Positive psychological constructs such as positive affect and meaning and purpose are related to resilience in the face of significant stress. No studies have examined these associations among a cohort of HCWs during this pandemic. The purpose of this study was to examine the association of depression, anxiety, positive affect, and meaning and purpose with burnout among HCWs during the COVID-19 pandemic. We utilized data from a cross-sectional survey conducted between September 29-December 8, 2021, among a cohort of 2,411 HCWs from a large, tertiary academic health care system in the Chicago area. We employed the Patient-Reported Outcomes Measurement Information System (PROMIS) measures for depression, anxiety, positive affect, and meaning and purpose and burnout was measured by the Oldenburg Burnout Inventory (OLBI). The majority (80.88%) of HCWs in this study identified as White, Non-Hispanic race/ethnicity, female sex (82.37%), and roughly one third were between ages 30-39 years old (30.98%). Registered nurses (26.96%) accounted for the largest single occupation group. The mean burnout score was 36.87 (SD= 7.65), with 53.38% of participants classified as having burnout, and registered nurses demonstrating the highest proportions of burnout (63.54%). Higher depression (coef= 0.15, SE= 0.03, p<0.001) and anxiety (coef= 0.25, SE= 0.02, p<0.001) scores were associated with higher burnout in multivariable linear regression models. Increased positive affect (coef= -0.19, SE= 0.02, p<0.001) and meaning and purpose (coef= -0.12, SE= 0.01, p<0.001) scores were significantly associated with reduced burnout. Positive affect and meaning and purpose were inversely associated with burnout among a cohort of HCWs during the COVID-19 pandemic. Previous studies of positive affect and meaning and purpose suggest the potential buffering effect that these indices may have on burnout. Future research is needed to examine the effect of positive affect and meaning and purpose on mitigating the negative impacts of burnout, depression, and anxiety among HCWs as they cope with the stress of the COVID-19 pandemic and beyond.